Bioeconomical solutions and investments in sustainable city development - Vargas-Hernández, José G.; Zdunek-Wielgołaska, Justyna Anna (IGI Global, 2019)
"This book expands the knowledge on the implementation of innovative solutions in cities and surrounding environment. It also highlights the role of green areas in the sustainable development of urban settings"...